Cultivation Process Optimization Of Recombinant Bacillus Subtilis Apoptin - MUHAMAD SAHLAN; YUKI DESIANDINI; MUHAMMAD IQBAL; NUNUK WIDHYASTUTI; AMARILA MALIK; SISWA SETYAHADI (Indonesian Society for microbiology, 2013)
The success of recombinan apoptin production in native form in the previous results open the way to develop this anticancer protein production to the larger scale. We optimized cultivation process of recombinant Bacillus subtilis 168 harbouring pOXGW12His8Arg with apoptin gene in a stirred tank fermentor and shake flasks. The parameters to optimize cultivation process are xylose-inducer concentration, agitation speed, and aeration rate. The xylose-inducer concentration variations are carried out in a shake flasks with 100 mL volume broth, while the agitation speed and aeration rate variation is carried out in a stirred tank fermentor with 3 L volume broth. The xylose concentration is varied between 0-5% w/v, while agitation speed and aeration rate are varied between 150-250 rpm and 0.5-1.5 NL min-1 respectively. The best condition in this cultivation is 1% w/v of xylose, 250 rpm of agitation speed and 1,5 NL min-1 of aeration rate giving the specific growth rate value for each parameter of 0.628 h-1; 0.630 h-1; and 0.747 h-1 respectively. The recombinant apoptin were purified by Ni-NTA column using AKTA system. However, the results showed that the optimum condition of producing recombinant apoptin was 1% w/v of xylose, 250 rpm of agitation speed, and 0.5 NL min-1 of aeration.